Aplikasi Ekstrak Padina minor dan Centella asiatica sebagai Biostimulan terhadap Pertumbuhan Tanaman Kedelai (Glycine max (L.) Merr.) - Suwirmen Suwirmen; Zozy Aneloi Noli; Titiek Rukmini (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Biostimulants are formulations of organic compounds derived from plants or microorganisms and can increase the efficiency of nutrient absorption, tolerance of abiotic stress and plant productivity. Padina minor contains high levels of macro and microelements, growth-regulating hormones and secondary metabolites. Centella asiatica contains secondary metabolites, essential oils, and amino acids. This study aims to determine the effect of seaweed extract Padina minor, Centella asiatica and a combination of extracts Padina minor and Centella asiatica on the growth of soybean plants grown on ultisol soil. This study used a completely randomized design (CRD) with 4 treatments with 6 replications. This treatment consisted of Padina minor, Centella asiatica and a combination of Padina minor and Centella asiatica. The results showed that the administration of Padina minor extract had an effect on increasing plant height, while Centella asiatica extract had an effect on leaf area and the combination of Padina minor and Centella asiatica extracts had an effect on increasing plant height, number of leaves, leaf area and wet weight of soybeans planted. on ultisols.